Physical and mathematical modelling of rib pillar deformation and failure processes - Lomakin, I.S.; Tsayukov, A.A.; Evseev, A.V. (Perm Federal Research Centre Journal, 2021)
Underground mining of water-soluble ores is associated with the necessity of mine protection from flooding. Reduction of risks of emergency situations at Perm Krai potash mining enterprises by means of real-time response to underground changes and by organizing appropriate preventive measures contributes to safe subsoil usage and the development of the region.The article presents the main results of research on experimental and theoretical justification for using relative transversal deformation of rib pillars as an informative parameter that allows a rapid assessment of underground mine load-carrying elements for Verkhnekamskoye potash deposit conditions. Experimental studies consisted of physical modelling of pillars deformation and failure processes on the basis of laboratory tests on uniaxial loading of salt rock cubic specimens of large sizes with simultaneous recording of their strain state. Theoretical studies included mathematical description of laboratory tests results and determination of medium model parameters that could reliably describe all stages of salt sample deformation. In order to estimate rib pillars relative transversal deformation values at which yield occurs the adaptation of developed model of medium to stoping room supporting elements taking into account their real size and geometrical form was carried out.